Reply to the 'Comment on "Robust scalable high throughput production of monodisperse drops"' by M. Nakajima, Lab Chip, 2017, 17, DOI: 10.1039/C7LC00181A. Issue 13 (12th June 2017) - Amstad, E.; Weitz, D. A.
Abstract : This reply to the comment by Nakajima highlights the differences between the microchannel step emulsification devices developed by the Nakajima group and the millipede device reported by us in Lab on a Chip . Abstract : This reply to the comment by Nakajima on our article that appeared in Lab on a Chip (E. Amstad, M. Chemama, M. Eggersdorfer, L. R. Arriaga, M. Brenner and D. A. Weitz, Lab Chip, 2016, 16, 4163–4172) highlights the differences between the microchannel step emulsification devices developed by the Nakajima group and the millipede device reported by us in Lab on a Chip .